GnRH Agonist versus hCG Trigger in Ovulation Induction with Intrauterine Insemination: A Randomized Controlled Trial - Minh Tam Le; Dac Nguyen Nguyen; Jessica Zolton; Vu Quoc Huy Nguyen; Quang Vinh Truong; Ngoc Thanh Cao; Alan Decherney; Micah J. Hill (International Journal of Endocrinology)
This study is aimed at comparing clinical pregnancy rates (CPRs) in patients who are administered either gonadotropin-releasing hormone agonist (GnRHa) or human chorionic gonadotropin (hCG) for ovulation trigger in intrauterine insemination (IUI) cycles. A prospective randomized comparative study was conducted at Hue University Hospital in Vietnam. A total of 197 infertile women were randomly assigned to receive either GnRHa trigger (n=98 cycles) or hCG trigger (n=99 cycles) for ovulation trigger. Patients returned for ultrasound monitoring 24 hours after IUI to confirm ovulation. A clinical pregnancy was defined as the presence of gestational sac with fetal cardiac activity. There was no difference in ovulation rates in either group receiving GnRHa or hCG trigger for ovulation. Biochemical and CPR were higher in patients who received hCG (28.3% and 23.2%) versus GnRHa (14.3% and 13.3%) (p=0.023, OR 0.42, 95%CI=0.21−0.86 and p=0.096, OR 0.51, 95%CI=0.24−1.07, respectively). After adjusting for body mass index (BMI) and infertility duration, there was no difference in CPR between the two groups (OR 0.58, 95% CI 0.27-1.25, p=0.163). In conclusion, the use of the GnRHa to trigger ovulation in patients undergoing ovulation induction may be considered in patients treated with IUI.